2004
DOI: 10.1042/bj20031014
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic phospholipase A2-p11 interaction controls arachidonic acid release as a function of epithelial cell confluence

Abstract: Madin-Darby canine kidney type II cells were shown to release low amounts of AA (arachidonic acid) and prostaglandin E2 in response to various stimuli when analysed after cell confluence. In contrast, non-confluent Madin-Darby canine kidney type II cells released much higher amounts of AA and prostaglandin E2. In both stationary and non-confluent cells, AA was released by type IV cPLA2 (cytosolic phospholipase A2), as shown by the use of specific inhibitors and by analysis of the profile of fatty acids release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The mechanism underlying this effect is not clear, although the results obtained with DTT and BEL indicate that BEL-sensitive iPLA 2 activity may be responsible for the impairment of AA release, whereas cPLA 2 activity was present in both nondifferentiated and differentiated Caco-2 cultures. In contrast, Bailleux et al (38) reported that the postconfluence decrease in [ 3 H]AA release depends on cPLA 2 activity in the case of Madin-Darby canine kidney type II and Caco-2 cultures.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism underlying this effect is not clear, although the results obtained with DTT and BEL indicate that BEL-sensitive iPLA 2 activity may be responsible for the impairment of AA release, whereas cPLA 2 activity was present in both nondifferentiated and differentiated Caco-2 cultures. In contrast, Bailleux et al (38) reported that the postconfluence decrease in [ 3 H]AA release depends on cPLA 2 activity in the case of Madin-Darby canine kidney type II and Caco-2 cultures.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, enzymes regulating fatty acid utilization are affected, based on two recent reports. Bailleux et al (22) observed that the attainment of confluency with the establishment of cell-to-cell contacts controlled the activation of the cytosolic form of phospholipase A 2 . This was a result of a stoichiometric change in the interaction of the phospholipase A 2 with the protein p11.…”
Section: Discussionmentioning
confidence: 99%
“…For experiments described thus far, cells were harvested at 24-48 h after 100% confluence. Because the degree of cell contact can affect fatty acid metabolism (22,23), the effect of cell density on fatty acid levels in 16HBE cells was examined (Fig. 4).…”
Section: Expression Of the Fatty Acid Defect Is Linked To Cftr Dysfunmentioning
confidence: 99%
“…Phosphorylation activates the enzyme but a rise in intracellular Ca 2+ , acting through the calcium-lipid binding domain, is needed to cause translocation of cPLA 2 from the cytosol to the membrane where it gains access to its substrate. However, recent studies have indicated that cPLA 2 interaction with other membrane lipids such as cholesterol, phosphatidylinositol bisphosphate, and ceramides, as well as interaction with proteins like annexins, p11 and vimentin, are needed for the complete activity of cPLA 2 [26,27]. Hence, the full story of the mechanisms of regulation of this enzyme during hibernation remains to be be determined as do the full range of metabolic consequences of cPLA 2 suppression.…”
Section: Discussionmentioning
confidence: 99%